Rush hour. - Ratner, Brett (Pasig City : Viva Video, 1999)
International superstar JACKIE CHAN is teamed with funnyman CHRIS TUCKER in this explosive thrill-a-minute adventure jam-packed with Chan's trademark daring martial arts stunts. In this exciting tale of betrayal and revenge, two men from very different worlds must learn to trust each other before they can win a high stakes battle against a ruthless enemy who threatens to demolish the fragile peace between their countries.